Report of the Working Group on Leather and Leather Goods Industry for the Tenth Five Year Plan (2002-2007) Volume I - Planning Commission (Planning Commission, 2001)
India enjoys an image of a source of good quality finished leathers in the global market. It has been estimated that about 10% of the world supply of leather is processed in India. However, the share of India in global leather trade is only about 3%. The fundamentals employed in the planning process for the Tenth Plan period aim at the enhancement of share of India in global leather trade to about 10% by the end of 2007. Although there have been several measures to increase the technology preparedness of the country during the previous plan periods, the level of investments into the sector have not been commensurate with the perceived goals and opportunities.
Government of India Planning Commission
Government of India Planning Commission